2013
DOI: 10.3109/14015439.2012.671357
|View full text |Cite
|
Sign up to set email alerts
|

Lingual frenectomy and alveolar tap production: An acoustic and perceptual study

Abstract: In this phonetic study, productions of the consonant in the stressed syllable position of the word arara as produced by 13 subjects with short and/or anterior lingual frenulum were compared before and after lingual frenectomy. The results from the measurement of the stressed consonant duration and from the identification of the consonant manners of articulation based on the inspection of spectral characteristics are discussed and related to the answers to a perceptual identification test. After surgery, the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…The study selection process is shown in Figure 1. In total, 16 studies 4,5,13,15‐27 with a total sample size of 2244 participants were included in this systematic review for further analysis. Figure 1 indicates a flowchart of the studies included in the selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study selection process is shown in Figure 1. In total, 16 studies 4,5,13,15‐27 with a total sample size of 2244 participants were included in this systematic review for further analysis. Figure 1 indicates a flowchart of the studies included in the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 16 included studies, three were RCTs 17,23,26 and 13 were observational studies (two case series, 19,20 one cross‐sectional study, 15 and 10 cohort studies including four retrospective studies 13,18,22,24 and six prospective studies) 4,5,16,21,25,27 . As for the regions, seven of 16 studies were conducted in the USA, 4,13,16,17,22,24,25 followed by two in Brazil, 20,21 and the remaining seven studies were conducted in the UK, 19 Australia, 27 Iran, 23 Japan, 5 Korea, 26 Spain, 15 and Tel Aviv 18 . The included studies were generally small, with a median enrollment of 34 participants.…”
Section: Resultsmentioning
confidence: 99%
“…The alveolar tap is of clinical interest, since the impairment of tap function would result in speech disorder, due to less amplitude of the articulators. (Camargo et al, 2013) Thus, the L, R, Z and S sound would be distorted due to the impairment function of linguo-alveolar articulatory target, and T, D, and N sound was distorted due to the impairment function of linguo-dental articulatory target. (Faria et al, 2019;Suzart & Carvalho, 2016;Walsh & McKenna Benoit, 2019) Given the lesion features of the case presented, greater the size of the lesion, the greater the chance of harming the positioning of the tongue and the lingual frenulum.…”
Section: Discussionmentioning
confidence: 99%
“…Marchesan et al, 2012 mostraram que após a frenectomia lingual, sujeitos com anquiloglossia apresentaram aumento da abertura de boca, bem como, movimentos mais precisos de língua, melhorando a fala. Vários outros estudos também apontaram que a cirurgia para liberação do frênulo lingual melhora a produção da fala (Ostapiuk, 2010); (Camargo et al, 2013(Camargo et al, /2016).…”
Section: Discussionunclassified